Synthesis of TiO2 hollow nanofibers by co-axial electrospinning and its superior lithium storage capability in full-cell assembly with olivine phosphate - Zhang, Xiang (2013)
We report the formation and extraordinary Li-storage properties of TiO2 hollow nanofibers by co-axial electrospinning in both half-cell and full-cell configurations. Li-insertion properties are first evaluated as anode in half-cell configuration (Li/TiO2 hollow nanofibers) and found reversible insertion of ~0.45 moles are feasible at current density of 100 mA g–1. The half-cell displayed a good cycleability and retained 84% of initial reversible capacity after 300 galvanostatic cycles. Full-cell is fabricated with commercially available olivine phase LiFePO4 cathode under optimized mass loadings. LiFePO4¬/TiO2 hollow nanofibers cell delivered the reversible capacity of 103 mAh g–1 at current density of 100 mA g–1 with operating potential of ~1.4 V. Excellent cycleability is noted for full-cell configuration irrespective of the applied current densities and retained 88% of the reversible capacity after 300 cycles in ambient conditions at current density of 100 mA g–1.